Biofumigation for the Management of Fusarium graminearum in a Wheat-Maize Rotation - Samina Ashiq; Simon Edwards; Andrew Watson; Matthew Back (Pathogens, 2022)
Fusarium graminearum is the most important causal agent of head blight in wheat, and stalk and ear rot in maize. A field experiment was conducted to investigate the effect of incorporation of Brassicaceae cover crops on Fusarium graminearum in a wheat-maize rotation. Five species belonging to Brassicaceae (Brassica juncea, Eruca sativa, Raphanus sativus, B. carinata, B. oleracea var. caulorapa L.) were used in the field experiment to investigate their potential to suppress F. graminearum inoculum in soil, disease incidence in maize and to reduce subsequent mycotoxin contamination in maize. Brassica juncea was found to contain the highest glucosinolate concentration in shoots (31 µmol g−1). Severity of ear rot and stalk rot in maize was not significantly reduced in the amended plots. Incorporation of R. sativus ‘Terranova’ significantly decreased the amount of F. graminearum DNA by 58% compared with the cultivated fallow treatment, however the DNA concentration was not significantly different to fallow uncultivated. Fusarium graminearum DNA and deoxynivalenol in maize was 50% lower after incorporation of B. oleracea var. caulorapa L. compared to after fallow treatment but the difference was not significant. The brassica crops used in the present field experiment were not effective in suppressing F. graminearum, therefore further studies to optimise the current approach are recommended.